2015
DOI: 10.1016/j.dld.2015.01.070
|View full text |Cite
|
Sign up to set email alerts
|

SerpinB3 and Yap interplay increases Myc oncogenic activity

Abstract: Primary liver cancer, mainly hepatocellular carcinoma (HCC), is one of the leading causes of cancer-related death worldwide 1 and generally has a poor prognosis since it is often diagnosed at an advanced stage when treatment is not effective. Great efforts have been made to decipher the molecular mechanisms of HCC and gene expression profiling has been used to identify subgroups of patients according to etiological factors, early pre-neoplastic lesions, stage of the disease, rate of recurrence and survival [2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…To address the mechanisms by which hepatocyte HIF‐2α up‐regulation promotes inflammatory mechanisms in NAFLD, we focused our attention on the role of HRGP, a hepatocyte‐released mediator (i.e., hepatokine) that has been recently shown to support liver macrophage activation in experimental and clinical NAFLD/NASH . To investigate the possible hypoxia‐dependent and HIF‐2α‐dependent modulation of HRGP, we employed HepG2 cells, which are known to rapidly respond to hypoxia with HIF‐2α stabilization and the up‐regulation of HIF‐2α target genes . Incubation of HepG2 cells under hypoxic conditions, which is known to rapidly promote the nuclear translocation of HIF‐2α, was associated with an appreciable increase in HRGP synthesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the mechanisms by which hepatocyte HIF‐2α up‐regulation promotes inflammatory mechanisms in NAFLD, we focused our attention on the role of HRGP, a hepatocyte‐released mediator (i.e., hepatokine) that has been recently shown to support liver macrophage activation in experimental and clinical NAFLD/NASH . To investigate the possible hypoxia‐dependent and HIF‐2α‐dependent modulation of HRGP, we employed HepG2 cells, which are known to rapidly respond to hypoxia with HIF‐2α stabilization and the up‐regulation of HIF‐2α target genes . Incubation of HepG2 cells under hypoxic conditions, which is known to rapidly promote the nuclear translocation of HIF‐2α, was associated with an appreciable increase in HRGP synthesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(32) To investigate the possible hypoxia-dependent and HIF-2a-dependent modulation of HRGP, we employed HepG2 cells, which are known to rapidly respond to hypoxia with HIF-2a stabilization and the up-regulation of HIF-2a target genes. (28,33) Incubation of HepG2 cells under hypoxic conditions, which is known to rapidly promote the nuclear translocation of HIF-2a, (28) was associated with an appreciable increase in HRGP synthesis (Fig. 5A).…”
Section: Hepatocyte-specific Deletion Of Hif-2a Prevents the Progressmentioning
confidence: 94%
“…Furthermore, it was recently confirmed that its expression correlates with that of TGF-B1 and that in fact, SERPINB3 contributes to TGFB1 overexpression and release [42] . So, far from its antiprotease activity, and its biomarker possibilities, SERPINB3 was suggested to be an oncoprotein in as much as it protects the cells from apoptosis and induces epithelial-mesenchymal transition, cell invasiveness and proliferation [43] .…”
Section: Serpinb3mentioning
confidence: 95%
“…[24] , 2014 mice transgenic for liver SerpinB3 showed higher liver regenerative ability compared to wild-type mice, supporting a role of this protein in promoting cell growth and proliferation [26] . Other mechanisms of tumor growth promotion induced by SerpinB3 include the up-regulation of Myc oncogene transcription with two different strategies [27] : the first mechanism is through the intracellular SerpinB3 antiprotease activity that blocks its cleavage exerted by Calpain, preventing the generation of the non-oncogenic cytoplasmic Mycnick form and allowing nuclear translocation of Myc with pro-oncogenic activity. The second one consists in the transcriptional induction of Myc, through the increase of Yap pathway [27] .…”
Section: Apoptosismentioning
confidence: 99%
“…Other mechanisms of tumor growth promotion induced by SerpinB3 include the up-regulation of Myc oncogene transcription with two different strategies [27] : the first mechanism is through the intracellular SerpinB3 antiprotease activity that blocks its cleavage exerted by Calpain, preventing the generation of the non-oncogenic cytoplasmic Mycnick form and allowing nuclear translocation of Myc with pro-oncogenic activity. The second one consists in the transcriptional induction of Myc, through the increase of Yap pathway [27] . Furthermore, recent findings indicate that SerpinB3/SerpinB4 isoforms are a Ras-responsive factor that plays an important role in Rasassociated cytokine production and tumorigenesis [28] .…”
Section: Apoptosismentioning
confidence: 99%